Clinical Management and Outcomes of Adrenal Hemorrhage Following Adrenal Vein Sampling in Primary Aldosteronism. Issue 1 (January 2016) - Monticone, Silvia; Satoh, Fumitoshi; Dietz, Anna S.; Goupil, Remi; Lang, Katharina; Pizzolo, Francesca; Gordon, Richard D.; Morimoto, Ryo; Reincke, Martin; Stowasser, Michael; Mulatero, Paolo
Abstract : Aldosterone-producing adenoma and bilateral adrenal hyperplasia account for >90% of all primary aldosteronism cases. Distinguishing between bilateral and unilateral disease is of fundamental importance because it allows targeted therapy. Adrenal vein sampling (AVS) is the only reliable means to preoperatively differentiate between unilateral and bilateral subtypes. A rare but serious complication of AVS is an adrenal hemorrhage (AH). We retrospectively examined in detail 24 cases of AH during AVS in 6 different referral hypertension centers. AH more often affected the right adrenal (n=18) than the left (n=5, P <0.001); 1 bilateral. Median duration of experience of the radiologist in AVS at the time of AH was 5.0 years (0.6–7.8) and AH occurred with both highly experienced (>10 years) and less experienced radiologists. Of 9 patients who suffered AH in the gland contralateral to an aldosterone-producing adenoma and who underwent complete (n=6) or partial (n=3) unilateral adrenalectomy, only one required long-term corticosteroid replacement for adrenal insufficiency. No reduction in blood pressure or biochemical resolution of primary aldosteronism occurred in any of those patients who experienced AH in the gland ipsilateral to an aldosterone-producing adenoma (n=6) or who had bilateral adrenal hyperplasia (n=9). No patient required invasive treatments to control bleeding or blood transfusion. In conclusion, AH usually has a positive outcome causing either no or minor effects on adrenal function, and AVS should remain the best approach to primary aldosteronism subtype differentiation. Abstract : Supplemental Digital Content is available in the text.